The mediating effects of resilience in the relationship of sexual involvement and romantic relationship dissolution - Chan, Siaw Leng; Lau, Poh Li (Universiti Putra Malaysia Press, 2021)
Romantic relationship dissolution (RRD) can be perceived as an upsetting or momentous event and the most stressful and unsettling events that one can encounter in life. The aim of this study to investigate the relationship between sexual involvement in a relationship and romantic relationship resolution and the role of resilience as mediators of this relationship. Two hundred ninety-three emerging young adults (ages 18 to 29) from Klang Valley have participated in this study. The present study used the Resilience Scale (RS), the Core Bereavement Items (CBI), and demographic information items. Obtained results indicated a significant difference in sexual involvement in a relationship on the level of reactions to romantic relationship dissolution. The sexual involvement in the relationship was positively and significantly correlated with romantic relationship dissolution. Specifically, sexual involvement was negatively correlated with resilience, which was, in turn, negatively associated with romantic relationship dissolution. Additionally, results also show that mediation effect for sexual involvement in resilience to romantic relationship resolution was significant. The practical implications for helping professionals were also discussed in this work.